The Advantages and Disadvantages of Livestock Manure and its Biochar as a Solid Fuel and Soil Amendment - Made Gunamantha; I Putu Parwata; I Gede Agus Beni Widana; Made Vivi Oviantari (Indonesian Journal of Environmental Management and Sustainability, 2022)
The aim of this study is to elucidate some of the basic characteristics of manure and its biochar and to explore its potential as a solid fuel and soil amendment. Cow, pig, chicken, and duck manure were selected and collected in the farmer’s pen. Furthermore, composite sampling was applied to obtain a representative sample of each manure. Each of them was dried in the sun for four to seven days, and each sample was divided into two parts. The first part was not further processed, while the rest were carbonized. Carbonization was carried out within a temperature range of 300 to 400?C and 4 h residence time. C-organic, N-total, available P and K, CEC, volatile matters, fixed carbon, ash content, Carbon (C), Hydrogen (H), Oxygen (O), Nitrogen (N), Sulfur (S) content), higher heating value, and the chemical composition of their ash in both original and carbonized manure were identified. In addition, the nutritional content was relatively comparable and the H/C and O/C ratio in biochar were lower than in its original state. Both the original and carbonized manure indicated low calorific value, while the ash content and fouling index were high. The results showed that livestock manure in both forms has more potential as a soil amendment than solid fuel.